Performance and emissions of a DI diesel engine fueled by different biodiesel blends - Alawi, Majed M. (My University, 2014)
Biodiesel has been a promising clean alternative fuel to fossil fuels, which reduces the emissions that are released by fossil fuels, and possibly reduces the energy crisis caused by the exhaustion of petroleum resources in the near future. Biodiesel is replacing diesel as an alternative fuel for internal combustion engines. Previous research studies have shown that biodiesel can greatly reduce carbon monoxide (CO), hydrocarbon (HC) and particulate matter (PM) emissions compared to diesel fuels, but very few studies have shown a reduction in total nitrogen oxides (NOx). At present, B20 (20% biodiesel in the total fuel mix) is being used commonly in the US due to its material compatibility to changing weather conditions, emission benefits and costs. Currently, Canada is planning to use 5% of biodiesel by 2015. The objective of this study is to test the feasibility of biodiesel in cold climates such as Canada. The biodiesel used is made of canola oil obtained from a local supermarket and winter diesel is used as a reference fuel. Three different series were used. The first series was biodiesel/diesel with six blends (B0, B5, B10, B20, B50 and B100). The second series was biodiesel/diesel plus 2% of a chemical additive (B0, B5A, B10A, B20A, B50A and B100A). The final was kerosene/biodiesel series (K0, K5, K10, K20, K50 and K100). Chemical additive (Wintron XC30) is used to lower the cloud point of the blends and this is the first attempt to investigate its effect on engine emissions. On the other hand, there are limited studies on kerosene being treated as a blending fuel, where it is mainly used to lower the cloud point of the blends to investigate the feasibility of biodiesel in a cold climate such as the winter season in Canada and suggest an appropriate solution for the future of biofuel. Engine performance and emission concentrations are investigated by determining the break specific fuel consumption (bsfc), fuel conversion efficiency and measuring emission concentrations of CO, HC, NO, NO2 and NOx using gas analysers. Engine tests are performed on a constant rated speed at three different load conditions. A comparison is made for the three series. Most of the blends have shown improved emissions compared to fossil diesel. B5A demonstrated a lower cloud point than fossil diesel, and the kerosene series showed excellent results at high load conditions.
Keywords: Biodiesel history; Production of biodiesel; Biodiesel properties; Biodiesel's emissions and performance